Penumbuh-kembangan Inovasi Melalui Laboratorium Inovasi Bagi Pemerintah Daerah di Indonesia - Desak Widhiatuti Srimarchea; Tri Noor Aziza (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2021)
Since the reforms in 1998 there have been changes in democracy, from centralized to decentralized and the existence of regional autonomy which gives freedom to each region to manage its own region. Freedom to increase the responsibilities of local governments must provide and improve services to the community. Therefore a breakthrough is needed. National Institute of Public Administration takes a role in accelerating the growth of governance innovation in the local government environment through the National Innovation Laboratory Program by assisting innovation in local government using the 5D instruments (Drum, Diagnosis, Design, Delivery and Display). There are two Locus Innovation Laboratories which are used as research namely Tanah Bumbu Regency in South Kalimantan Province and Kotawaringin Regency in Kalimantan Province, Central Kalimantan. With the descriptive analysis method through library research, this study wants to see the advantage by the innovation laboratory in terms of innovation development in the regions. The results of the analysis show through laboratory assistance, the region get advantage from open mindedness of apparatus, and change the way people think about government performance and bring up trust towards local government. Keywords:innovation, local government, innovation laboratory